Unravelling aid funding: Linking funding allocation patterns and localization in Sierra Leone - Swetha Ramachandran (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
Development assistance funding by international donors is rarely channelled to/through local actors. While there are strong normative and practical arguments for localizing funding, progress has been piecemeal as donors are largely left to their own devices to decide how, when, where, and how much to localize. This paper explores the antecedents to donor aid allocation and poses the question: 'How and why do donors vary in their extent of localization (as defined by the use of local channels to disburse aid funding)?'. Using the case of aid-dependent Sierra Leone and applying a mixed-methods design combining primary interviews with analysis of the Development Assistance Database, I find that projects funded by multilateral donors are more likely to be localized than those of bilateral donors, who prioritize funnelling aid through actors from their home countries. I also find that the nature of aid assistance (i.e. whether funding is provided through loans or grants) significantly determines the extent to which local channels are used. Lastly, I show that these trends manifest at the sectoral level,where sectors dominated by bilateral donors often use parallel implementation structures, while sectors dominated by multilateral donors see greater usage of local channels and capacities. Additionally, while projects by multilateral donors may appear more localized, I find no evidence that such projects are more impactful or participatory than projects funded by other donor types.
Keywords: F35; F59; 330; development assistance; localization; aid channels; mixed methods; Sierra Leone